PROGNOSTIC SIGNIFICANCE OF FLUORESCAMINE LABELED SERUM ALBUMIN AND GLOBULIN VALUES IN PATIENTS WITH DIABETES MELLITUS RESULTS IN END STAGE RENAL DISEASES - SHUBI JAMAL; Y.K. AGRAWAL (International Journal of Pharma and Bio Sciences, 2013)
Proteinurea is considered to be major prognostic factor in patients with certain chronic diseases, such as cancer and ESRD. High serum albumin, gamma globulin, beta-2 & alpha-1 microglobulin is common in patients with diabetes mellitus; nevertheless, the relationship between proteinuria and diabetes mellitus prognosis has not been verified. The mean arterial pressure was 30±9%. The mean serum albumin and globulin was 186.9±0.5mg/day. Patients with and without high urinary albumin levels were similar in age, because of diabetes mellitus. The survival rate of patients with proteinuria was 50.41% and 80.62% in those without proteinuria(P<0.001). The calibration curve for four specific proteins responsible for ESRD in diabetes was found linear in the range of 10-9 to 103nmolL-1, correlation coefficient(r2) was found to be 0.9926. The LOD and LOQ were observed as 3.28nmolL-1 to 23.80nmolL-1. To elucidate the effect of labeled serum albumin and globulin level on prognosis of patients with diabetes mellitus results in ESRD.